Hasil Belajar Fisika dengan Menggunakan Media Phet Simulation - Yanti, Resky Perdana (Indonesian Journal of Pedagogical and Social Sciences, 2024)
Abstract. This research aims to improve the physics learning outcomes of class XI students by using PhET simulation media. The type of research carried out was classroom action research with three cycles. There are five stages in this research, including the preparation stage, planning stage, implementation stage, observation and monitoring stage, and reflection stage. There are two types of instruments used in research, namely quantitative and qualitative. Quantitative instruments in the form of questionnaires and academic ability tests. Student questionnaires are given at the end of each cycle, questionnaires for teachers are given at the beginning and are used in analyzing teacher needs. Meanwhile, qualitative instruments use learning observations, interviews, field notes and documentation analysis. With research subjects totaling 32 students. After the cycle the class average was 65,7 but had not yet reached the KKM so cycle II was carried out. From the second cycle, the class average was obtained at 68,9, this increase also did not meet the KKM, so the third cycle was carried out and the class average was 78,6. Based on these data, it can be concluded that the use of PhET simulation learning media can improve the learning outcomes of class XI IPA 2 students at SMA Negeri 1 Selayar. Keywords: PhET Simulation, classroom action research, learning outcomes